Superstitious Practices Among Nupe Muslims In Niger State: Causes, Consequences And Islamic Perspectives On Solutions For Religious Development - Saheed Adewale Badmus; Hannatu Ahmed; Maryam Talatu Umar (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Superstitious practices continue to permeate some segments of Nupe Muslims communities in Niger State, Nigeria, despite Islamic strong emphasis on monotheistic teaching and rational belief. This paper explores the root causes-such as ignorance of Islamic teachings, cultural syncretism, poverty, and inadequate religious leadership-as well as the socio-religious, economic, and developmental consequences of these practices. Islamic corrective measures grounded in Tawhīd, Da’wah, and community-based education; alongside relevant government policy interventions were explored. Employing a review of literature and qualitative field evidence, the study argues that tackling superstition through integrated religious and policy frameworks can foster moral renewal, improve social cohesion, and enhance productivity, and support national development. Suggestions among others that include establishment of Qur’anic counselling and guidance centres, economic empowerment to reduce dependence on spiritual exploiters, collaborative initiative among Islamic Scholars, policymakers, and community leaders to design culturally sensitive educational programs, enforce health and socio-economics policies, and reinforce authentic Islamic values, thereby catalysing sustainable progress are hereby made.